PLANNING OF ECO-DRAINAGE SYSTEM TROUGH THE IMPLEMENTATION OF INFILTRATION WELLS IN THE TUNJUNGSEKAR AREA - Refa Alana Syalwa Saputra; Ayisya Cindy Harifa (Jurusan Teknik Sipil Politeknik Negeri Malang, 2026)
The Tunjungsekar area is a densely populated region with residential settlements, facing hydrological problems due to the increase in impervious areas and a conventional drainage system that cannot optimally accommodate the rainfall runoff. To mitigate these issues and maintain groundwater quality to prevent contamination from wastewater, environmentally friendly urban drainage is implemented by constructing infiltration wells. The purpose of this study is to redesign the drainage system, calculate flood discharge, plan the dimensions of new channels, design the dimensions of the infiltration wells, and calculate the required costs. This planning uses rainfall data collected from three stations: Singosari, Ciliwung, and Karangploso from 2015 to 2024. Other data used include topographic maps, site layouts, soil data, and the HSPK Malang city data for 2024. Rainfall data is analyzed using the Log Pearson Type III method with a recurrence interval of 10 years. The design rainfall was obtained at 140.50 mm, and cumulative flow rates ranged from approximately 0.01 m^3/sec to 0.07 m^3/sec using the rational method. Based on the analysis results, the dimensions of the new rectangular channel were found to be 30 cm and height is 50 cm. The type of channel used is a U-Ditch equipped with inlets, manholes, and culverts. The construction of infiltration wells uses brick masonry with a diameter ranging of 20 cm to 45 cm and a height of 100 cm, totaling 15 units, built scattered in the midst of the channel. The construction cost amounted to Rp509,820,000.00.